Systematic review and meta-analysis: risk factors for psoriatic arthritis. Part 1. - N. O. Pereverzina; L. S. Kruglova; T. V. Korotaeva; A. M. Lila (Современная ревматология, 2022)
According to epidemiological and clinical studies, every fourth patient with psoriasis develops psoriatic arthritis (PsA), and in many cases there is a destructive form of arthritis that leads to disability. Late diagnosis of PsA is associated with a significant reduction in the effectiveness of therapy. Therefore, early diagnosis of this disease is so important.Objective: to determine the methods for early detection of PsA, in particular the identification of risk factors (RFs) for its development, which will prevent the progression of the disease and the disability of patients.Materials and methods. The literature review and meta-analysis is presented in two parts. Part 1 of the systematic review included articles on exogenous RFs for the development of PsA published over the past 10 years.PubMed (MEDLINE), EMBASE, and Google Scholar databases were searched for articles published before March 1, 2021. We searched for currently registered trials in the registers of clinical trials of US (ClinicalTrials.gov), of China (Chinese Clinical Trial Registry) and the WHO InternationalClinical Trial Registry Platform. The statistical analysis was prepared in accordance with the international guidelines for systematic reviews and meta-analysis (PRISMA) using the Statistic SPSS 26.0 program (USA).Results and discussion. 957 articles published up to March 1, 2021 were identified. After further analysis, irrelevant articles were excluded. A total of 73 articles were included in the review and analysis, 32 of which were included in Part 1. The most common exogenous RFs are: mechanical injuries, medications, and psychotraumatic situations.Conclusion. PsA is a multifactorial disease. Currently, a large number of exogenous RFs for the development of this disease have been established. Knowledge of RFs and the ability to recognize them will help dermatovenereologists and rheumatologists to effectively assess and predict the patient's condition. Correction of modifiable RFs, early prescription of appropriate therapy will help to reduce the number of PsA cases, the development of functional disorders and prevent the growth of disability. However, studies on the comprehensive assessment of RFs in PsA are still insufficient. Further study of methods for the early diagnosis of PsA is needed in order to optimize its treatment.